Signal transduction induced in Trypanosoma cruzi metacyclic trypomastigotes during the invasion of mammalian cells - N. Yoshida; S. Favoreto Jr.; A.T. Ferreira; P.M. Manque (Brazilian Journal of Medical and Biological Research, 2000)
Penetration of Trypanosoma cruzi into mammalian cells depends on the activation of the parasite's protein tyrosine kinase and on the increase in cytosolic Ca2+ concentration. We used metacyclic trypomastigotes, the T. cruzi developmental forms that initiate infection in mammalian hosts, to investigate the association of these two events and to identify the various components of the parasite signal transduction pathway involved in host cell invasion. We have found that i) both the protein tyrosine kinase activation, as measured by phosphorylation of a 175-kDa protein (p175), and Ca2+ mobilization were induced in the metacyclic forms by the HeLa cell extract but not by the extract of T. cruzi-resistant K562 cells; ii) treatment of parasites with the tyrosine kinase inhibitor genistein blocked both p175 phosphorylation and the increase in cytosolic Ca2+ concentration; iii) the recombinant protein J18, which contains the full-length sequence of gp82, a metacyclic stage surface glycoprotein involved in target cell invasion, interfered with tyrosine kinase and Ca2+ responses, whereas the monoclonal antibody 3F6 directed at gp82 induced parasite p175 phosphorylation and Ca2+ mobilization; iv) treatment of metacyclic forms with phospholipase C inhibitor U73122 blocked Ca2+ signaling and impaired the ability of the parasites to enter HeLa cells, and v) drugs such as heparin, a competitive IP3-receptor blocker, caffeine, which affects Ca2+ release from IP3-sensitive stores, in addition to thapsigargin, which depletes intracellular Ca2+ compartments and lithium ion, reduced the parasite infectivity. Taken together, these data suggest that protein tyrosine kinase, phospholipase C and IP3 are involved in the signaling cascade that is initiated on the parasite cell surface by gp82 and leads to Ca2+ mobilization required for target cell invasion.